2020
DOI: 10.1021/acs.cgd.0c00833
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hierarchically Layered Cu-Rich Silicide Nanoarchitectures

Abstract: A solution-based synthesis of well-ordered Cu-rich silicide nanoarchitectures, consisting of a pair of layered cups and stems (ρ-Cu 15 Si 4 ), is demonstrated. The as-grown ρ-Cu 15 Si 4 typically exhibits distinct interconnected 1D stems consisting of a stack of nanorods (∼300 nm in length) terminated with concave hexagonal 3D cups that evolve through a self-regulated layer-by-layer growth mechanism. Discrete-time ex situ experimental observations reveal that the ρ-Cu 15 Si 4 evolution is driven by interatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…HRTEM of Si@CuSiNW revealed corresponding d-spacings of ≈0.62 and ≈0.28 nm of the CuSi NW core, in agreement with previous reports on Cu 15 Si 4 . [30,89] Additionally, HRTEM imaging of the Si@SiNW core confirmed Si with a lattice spacing of ≈0.32 nm, in line with previous reports on crystalline Si (Figure S9, Supporting Information). [67,90] The population density of Si NW branches along host Si NWs was found to vary widely, with the ratio of host NWs to NW branches (hNW-bNW) dependent on both the length and diameter of Si NW stems.…”
Section: Resultssupporting
confidence: 89%
“…HRTEM of Si@CuSiNW revealed corresponding d-spacings of ≈0.62 and ≈0.28 nm of the CuSi NW core, in agreement with previous reports on Cu 15 Si 4 . [30,89] Additionally, HRTEM imaging of the Si@SiNW core confirmed Si with a lattice spacing of ≈0.32 nm, in line with previous reports on crystalline Si (Figure S9, Supporting Information). [67,90] The population density of Si NW branches along host Si NWs was found to vary widely, with the ratio of host NWs to NW branches (hNW-bNW) dependent on both the length and diameter of Si NW stems.…”
Section: Resultssupporting
confidence: 89%
“…: 00‐001‐0802), along with Cu, Cu 15 Si 4, and Cu 0.83 Si 0.17 in agreement with the previous reports. [ 10b,11a,13,15 ] The additional reflections of Cu 0.83 Si 0.17 in XRD and absence of this phase in the TEM analysis of nanowire suggest that it only exists in a preformed silicide layer on the Cu foil surface prior to the Cu 15 Si 4 nanowire growth, [ 11a,16 ] and that is the reason it was not identified the HRTEM analysis of NWs (Figure 1j). The Raman spectrum of the Sb@Cu 15 Si 4 NW array shown in Figure S3 (Supporting Information) displays two peaks at 146.3 and 110 cm −1 which are attributed to the A 1g and E g bands of Sb, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We have confirmed that no pattern formation is observed when the rate of deposition was increased to 5 Å s −1 . Second, the AFM studies have shown that the total thickness of a particular island was found to be ∼ 150 nm, implying the initial formation of Cu 3 Si layer impedes further diffusion of Cu into the Si which gives the top layer of the islands as pure Cu [18,54].…”
Section: Understanding Growth Behaviourmentioning
confidence: 99%
“…Ordered 2-dimensional (2D) Cu nanostructures on Si(111) have been reported for very low thicknesses by Zang et al [16]. In the recent years, a huge volume of work has been reported on diffusion studies of Cu in Si substrates [1741]. In most of the studies on the growth of Cu nanostructures on the silicon substrate, the films are deposited at room temperature and post annealed for preparation of nanostructures.…”
Section: Introductionmentioning
confidence: 99%